Retrospective Evaluation of Bayesian Risk Models of LVAD Mortality at a Single Implant Center - Lohmueller, Lisa C.; Kanwar, Manreet K.; Bailey, Stephen; Murali, Srinivas; Antaki, James F. (Frontiers in Medicine, 2018)
Use of a left ventricular assist device (LVAD) can benefit patients with end stage heart failure, but only with careful patient selection. In this study, Bayesian network models for predicting LVAD patient mortality at 1, 3, and 12 months post-implant were evaluated on retrospective data from a single implant center. The performance of these models was better than the original model validation at all three time points, with receiver operating characteristic areas under the curves (ROC AUCs) of 78%, 76%, and 75%, respectively. The difference in performance may be due to a combination of institutional experience and patient disease severity. This evaluation of model performance verifies their utility for prospective decision making at this institution.